The evolution of pollen germination timing in flowering plants: Austrobaileya scandens (Austrobaileyaceae) - Williams, Joseph H. (Oxford University Press, 2012)
BACKGROUND AND AIMS: The pollination to fertilization process (progamic phase) is thought to have become greatly abbreviated with the origin of flowering plants. In order to understand what developmental mechanisms enabled the speeding of fertilization, comparative data are needed from across the group, especially from early-divergent lineages. I studied the pollen germination process of Austrobaileya scandens, a perennial vine endemic to the Wet Tropics area of northeastern Queensland, Australia, and a member of the ancient angiosperm lineage, Austrobaileyales. METHODOLOGY: I used in vivo and in vitro hand pollinations and timed collections to study development from late pollen maturation to just after germination. Then I compared the contribution of pollen germination timing to progamic phase duration in 131 angiosperm species (65 families). PRINCIPAL FINDINGS: Mature pollen of Austrobaileya was bicellular, starchless and moderately dehydrated—water content was 31.5 % by weight and volume increased by 57.9 % upon hydration. A callose layer in the inner intine appeared only after pollination. In vivo pollen germination followed a logarithmic curve, rising from 28 % at 1 hour after pollination (hap) to 97 % at 12 hap (R(2) = 0.98). Sufficient pollen germination to fertilize all ovules was predicted to have occurred within 62 min. Across angiosperms, pollen germination ranged from 1 min to >60 h long and required 8.3 ± 9.8 % of the total duration of the progamic phase. SIGNIFICANCE: Pollen of Austrobaileya has many plesiomorphic features that are thought to prolong germination. Yet its germination is quite fast for species with desiccation-tolerant pollen (range: <1 to 60 h). Austrobaileya and other early-divergent angiosperms have relatively rapid pollen germination and short progamic phases, comparable to those of many insect-pollinated monocots and eudicots. These results suggest that both the pollen germination and pollen tube growth periods were marked by acceleration of developmental processes early in angiosperm history.